Recent advances in baculoviral inhibitor of apoptosis - YU Wei; WU Yu-cheng; JIN Yong-feng; ZHANG Yao-zhou (浙江大学学报. 农业与生命科学版)
Apoptosis is an active process of cellular self-destruction that is involved in normal development. Two kinds of anti-apoptosis genes p35 and iap have been identified in baculovirus genome. Both of them function at different point in the death pathway. Extensive studies have been made about the structures and function mechanisms of the genes and their products. This review highlights the recent advances in the researches of the genes and their function mechanisms and explores the possible utilizations in the future.